2003
DOI: 10.1091/mbc.e02-03-0155
|View full text |Cite
|
Sign up to set email alerts
|

The Microtubule Plus-End Proteins EB1 and Dynactin Have Differential Effects on Microtubule Polymerization

Abstract: Several microtubule-binding proteins including EB1, dynactin, APC, and CLIP-170 localize to the plus-ends of growing microtubules. Although these proteins can bind to microtubules independently, evidence for interactions among them has led to the hypothesis of a plus-end complex. Here we clarify the interaction between EB1 and dynactin and show that EB1 binds directly to the N-terminus of the p150Glued subunit. One function of a plus-end complex may be to regulate microtubule dynamics. Overexpression of either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 164 publications
(159 citation statements)
references
References 44 publications
12
147
0
Order By: Relevance
“…microtubule plus-ends As CLIP-170 and EB1 co-localize to dynamic microtubule plus ends in the cell, we tested whether these two proteins may interact directly, similar to our previous observation that EB1 binds to the related N-terminal CAP-Gly domain of p150 Glued [17]. We found that recombinant EB1 was specifically retained on a CLIP-170-H2 column but not on a BSA control column (Fig.…”
Section: Clip-170 Binds Directly To Eb1 and Recruits Eb1 Tosupporting
confidence: 61%
See 3 more Smart Citations
“…microtubule plus-ends As CLIP-170 and EB1 co-localize to dynamic microtubule plus ends in the cell, we tested whether these two proteins may interact directly, similar to our previous observation that EB1 binds to the related N-terminal CAP-Gly domain of p150 Glued [17]. We found that recombinant EB1 was specifically retained on a CLIP-170-H2 column but not on a BSA control column (Fig.…”
Section: Clip-170 Binds Directly To Eb1 and Recruits Eb1 Tosupporting
confidence: 61%
“…Recombinant constructs of CLIP-170 (an in-frame T7 tag was fused to the N-terminus of the previously characterized H2 construct [16] generously provided by Holly Goodson, Notre Dame University) and p150 Glued (residues 1-333) [17], which span the microtubule binding domains of these proteins, as well as full length EB1 [17], were expressed as His-tagged fusion proteins in E. coli and purified by Ni 2+ -chromatography.…”
Section: Generation Of Recombinant Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…EBs recruit a multitude of other plus‐end tracking proteins (Akhmanova & Steinmetz, 2015), including dynactin, which is additionally required for plus‐end tracking of dynein in cells (Vaughan et al , 1999; Ligon et al , 2003; Dixit et al , 2008). The critical dynactin subunit for plus‐end tracking is p150 Glued (called p150 here).…”
Section: Introductionmentioning
confidence: 99%